Political Connection and Tax Avoidance: Evidence from Indonesia - Susanti; Pranyoto, Edi; Sartika Putri, Anandha; Elhando Badri , Rico (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the positive influence of political connections, the negative influence of managerial ownership, the negative influence of institutional ownership, the negative influence of the board of commissioners, the negative influence of the audit committee, and the negative effect of audit quality on corporate tax avoidance. The method used to test the model is to use panel data regression. The results of the study are political connections show a significant positive coefficient on tax avoidance, while managerial ownership, institutional ownership, and independent commissioners do not have a significant positive effect on tax avoidance, but audit committee and audit quality are not significantly negative related to tax avoidance. This means that political connections cause companies to do tax avoidance and corporate governance does not necessarily reduce tax avoidance.